2017
DOI: 10.1007/978-3-662-55665-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Topo-Logic as a Dynamic-Epistemic Logic

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…The arbitrary announcement modality ϕ capturing "stability of the truth of ϕ after any announcement" comes close to the intuition behind the effort modality ϕ as "stability of the truth of ϕ after any effort". In Baltag et al (2017), these two modalities are even proven to be equivalent in the single-agent setting. However, the appropriate interpretation of effort in the multi-agent setting and its connection to the arbitrary announcement modality still remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arbitrary announcement modality ϕ capturing "stability of the truth of ϕ after any announcement" comes close to the intuition behind the effort modality ϕ as "stability of the truth of ϕ after any effort". In Baltag et al (2017), these two modalities are even proven to be equivalent in the single-agent setting. However, the appropriate interpretation of effort in the multi-agent setting and its connection to the arbitrary announcement modality still remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Baltag et al (2017) later showed that, in spite of their different readings, the arbitrary announcement modality and the effort modality are equivalent in the single-agent case on topological spaces.…”
Section: Introductionmentioning
confidence: 99%
“…And a variety of logical models for evidence and belief update assume that each piece of evidence corresponds to a set of possible worlds U and entails exactly those propositions ϕ such that U ⊆ [[ϕ]] [24,14,26,9,7,8]. Of special note are those models in which the collection of evidence is assumed to take the structure of a topology [6,12,11,2,25]; the framework we propose can be viewed as a generalization of this paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the intuitive connections between SSL and the informational attitudes studied in DEL, connecting SSL to DEL is not entirely straightforward, even in the relatively simple case of public announcements. Connections between single-agent public announcement logic and SSL were made in [1,7,[10][11][12]36]. To the best of our knowledge, Wáng andÅgotnes [36] were the first to propose semantics for public announcements on subset spaces in terms of open set refinement rather than model restriction.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [30], we further extended the proposal in [12] with the arbitrary public announcement modality capturing information change caused by any announcement (rather than any effort) and studied a particular type of 'effort' that is in the shape of public announcements. Baltag et al [7] further investigated the relationship between the dynamic notions effort, public announcements, and arbitrary announcements, building on the settings presented in [12,30]. While the standard requirement for a truthful public announcement in DEL literature is only that it be true, the precondition int(ϕ) is stronger than ϕ simply being true (see also [12]) and it states that "ϕ is supported by truthful observation".…”
Section: Introductionmentioning
confidence: 99%